Mekanisme Corporate Governance pada Sustainability Reporting - Dewi, Ni Kadek Riska Santika; Sudana, I Putu (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p07, 2024)
This research aims to determine the influence of corporate governance mechanisms on the intensity of sustainability reporting. This research was conducted on banking subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. Sample selection was carried out using a purposive method. There were 14 companies that met the criteria as research samples so that the research data amounted to 42 observations. This research uses panel data regression analysis. The research results show that the board of directors has a positive effect on sustainability reporting. This is in accordance with agency theory which shows that the involvement of the board of directors is able to have an impact on the company's management function, including sustainability reporting, and the proportion of institutional ownership shows a positive influence, which means that institutional share ownership is able to strengthen the supervisory function of company management so that performance is optimal, while independent commissioners and committees audit, managerial ownership has no effect on sustainability reporting. Keywords: Corporate Governance Mechanism; Sustainability Reporting